A review of resilience in urban form for natural disaster-prone areas - Senjana, Suci; Handayani, Wiwandari; Suprapti, Atik (Spatium, 2024)
Considering resilience within the components of urban form can aid in the planning of disaster-prone cities and enable them to become more resilient. Although prior research has explored resilience and urban form, the aspects of urban form that can enhance natural disaster resilience remain relatively underexplored. Thus, this study aims to identify these aspects and explore research opportunities in the development of resilience concepts in urban form that have been previously studied by researchers. This study employs the systematic review method, which includes bibliometric analysis and a full-text review of the identified literature. The results show that plots, open spaces, buildings, and streets are the main variables in developing a resilient urban form. Additionally, the street network within the urban form is emphasized in emergency disaster planning. Most current research describes resilience in terms of the ability to withstand and adapt by restoring and operating systems as they were before the disaster occurred. Recommendations for future research include focusing on long-term resilience in urban form by implementing new operational methods in cities to achieve transformative adaptation. Another opportunity is to conduct research in locations with unique characteristics in developing countries, especially areas that have previously experienced significant natural disasters. This study contributes to the understanding of how urban form can be enhanced for resilience through the planning of its components.